Brand Alignment Targeting against the Needs of Gen-Z Consumers to Improve Brand Identity and Brand Advocacy - Sekarningtyas, Aldila Kinanti; Usman, Usman (Almana : Jurnal Manajemen dan Bisnis, 2023)
The phenomenon of online transportation in Indonesia has indeed been rampant for the last ten years due to increasingly sophisticated technological developments. The presence of PT Gojek Indonesia as a startup engaged in the field of online transportation has received a positive response from Gen-Z circles. This can be seen from the several services that PT Gojek Indonesia continues to develop so that in the end, there are 22 on-demand services that users can enjoy. This study aims to determine the indicators of Gen-Z consumer needs preferences in measuring brand alignment and how PT Gojek Indonesia will carry out the strategy to create the brand identity and brand advocacy for Gen-Z. The quantitative method used in this research uses the Partial Least Square Structural Equation Model (PLS-SEM) analysis technique. The critical finding of this study is that three exogenous variables (Brand Alignment, Brand Identity, and Brand Advocacy) positively and significantly affect consumer needs. However, this study has yet to explore consumer needs by adopting a comprehensive theory. Therefore, future research on brand alignment, identity, and advocacy, should discuss in more detail the sides of consumer needs by taking into account relevant theories, such as Maslow’s theory of markets and consumer behavior.